SeDiCI: Servicio de Difusión de la Creación Intelectual (Intellectual Creativity Diffusion Service) - De Giusti, Marisa Raquel (2008)
Universidad Nacional de La Plata (UNLP) Intellectual Creativity Diffusion Service (SeDiCI) was formed mainly to publicise the knowledge acquired at the different academic areas of our university, having the goal of restoring to the community the efforts expended on public university.